2016
DOI: 10.1039/c5cp06195d
|View full text |Cite
|
Sign up to set email alerts
|

Excited state structural evolution during charge-transfer reactions in betaine-30

Abstract: Ultrafast photo-induced charge-transfer reactions are fundamental to a number of photovoltaic and photocatalytic devices, yet the multidimensional nature of the reaction coordinate makes these processes difficult to model theoretically. Here we use femtosecond stimulated Raman spectroscopy to probe experimentally the structural changes occurring following photoexcitation in betaine-30, a canonical intramolecular charge-transfer complex. We observe changes in vibrational mode frequencies and amplitudes on the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 37 publications
(44 reference statements)
1
14
0
Order By: Relevance
“…We generated the three pulses required for FSRS with the 4.4 W output of a Coherent Libra-F-1K femtosecond amplifier. 32 We used a home-built non-collinear parametric amplifier to generate the actinic pump. The 2 μW white light seed continuum was generated in a 2 mm sapphire crystal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We generated the three pulses required for FSRS with the 4.4 W output of a Coherent Libra-F-1K femtosecond amplifier. 32 We used a home-built non-collinear parametric amplifier to generate the actinic pump. The 2 μW white light seed continuum was generated in a 2 mm sapphire crystal.…”
Section: Methodsmentioning
confidence: 99%
“… 29 When coupled with an actinic pump to promote photoexcitation, FSRS has been used to examine ultrafast excited state dynamics in systems such as solution phase biological samples, charge-transfer complexes, and solvatochromatic dyes. 30 32 FSRS has also been used to study several solid state systems including polymeric semiconductors, polystyrene beads, and dye-sensitized inorganic colloids. 33 35 As compared to time-domain ultrafast Raman techniques such as that used in ref.…”
Section: Introductionmentioning
confidence: 99%
“… 5,6 As a matter of fact, several studies on sustainable charge transfer systems employing organic molecules are emerging to increase their potential light harvesting capabilities to replace costly rare-earth metals and/or toxic materials, trying to understand how they can better generate excitons and other charge separated species. 7 Electronic charge separation can be photoinduced at the interface between two materials 8,9 in conjugated polymers, 10,11 intra- 12–15 or intermolecularly 16,17 and in metal–ligand coordination complexes. 18–20 A particular class of molecular compounds undergoing intermolecular CT is that of non-covalent π-stacked CT complexes, which are intensely colored molecular systems showing a weak interaction of a π-electron donor (D) and π-electron acceptor (A).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the interaction between the orthogonal conformation of D–A moieties is negligible due to broken π-electron conjugation, while the conformation can be changed under photoexcitation or mechanical stimuli, resulting in an overlap of the frontier orbitals between donor and acceptor and the formation of charge transfer state. Therefore, establishing how the D–A geometry influences the π-conjugated intramolecular charge transfer (ICT) property is crucial for their applications. To provide detailed molecular conformational changes occurring during ICT, femtosecond stimulated Raman spectroscopy (FSRS) has been used to track the reaction coordinate that drives the formation of ICT in several D–A molecular systems with a broad detection range and sufficiently high spectral and high temporal resolutions. , …”
Section: Introductionmentioning
confidence: 99%